2010
DOI: 10.1088/0004-637x/716/2/1531
|View full text |Cite
|
Sign up to set email alerts
|

ANALYZING THE LOW STATE OF EF ERIDANI WITHHUBBLE SPACE TELESCOPEULTRAVIOLET SPECTRA

Abstract: Time-resolved spectra throughout the orbit of EF Eri during its low accretion state were obtained with the Solar Blind Channel on the Advanced Camera for Surveys onboard the Hubble Space Telescope. The overall spectral distribution exhibits peaks at 1500 and 1700Å, while the UV light curves display a quasisinusoidal modulation over the binary orbit. Models of white dwarfs with a hot spot and cyclotron emission were attempted to fit the spectral variations throughout the orbit. A non-magnetic white dwarf with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…The hotspot on the white dwarf results from the shock region where the material from the MS star is accreted on to the white dwarf along the magnetic field lines. See, for example, the folded light curve of the known low-state polar EF Eri (Szkody et al 2010 ) which looks very similar to this one. To confirm this classification, we obtained the spectrum shown in Fig.…”
Section: Notes On Individual Objectssupporting
confidence: 57%
“…The hotspot on the white dwarf results from the shock region where the material from the MS star is accreted on to the white dwarf along the magnetic field lines. See, for example, the folded light curve of the known low-state polar EF Eri (Szkody et al 2010 ) which looks very similar to this one. To confirm this classification, we obtained the spectrum shown in Fig.…”
Section: Notes On Individual Objectssupporting
confidence: 57%
“…The final object in our survey is EF Eri, a very short period (P orb = 81.0 min) polar that has been stuck in a prolonged low state for more than a decade (see Szkody et al 2010 and references therein). Campbell et al (2008b) modeled phaseresolved near-IR spectra of EF Eri and found that cyclotron emission from accretion onto a 12.6 MG field dominated the luminosity of the system at those wavelengths.…”
Section: Ef Eridanimentioning
confidence: 99%
“…The green spectrum is the average of the JHK spectra presented in Campbell et al (2008b). curves-EF Eri exhibits large variations at all wavelengths, from the GALEX NUV (see Szkody et al 2010) to the near-IR. As shown in Figure 14, this variability continues into the mid-IR: the WISE W1 and W2 (not shown) and the Spitzer S2 light curves all show large amplitude variations of the same scale as that seen in the H-and K-band light curves.…”
Section: Ef Eridanimentioning
confidence: 99%
“…Accretion-heated spots that exceed the temperature of the underlying white dwarf by several 1000 K are frequently observed in polars, i.e. strongly magnetic CVs, and cause a modulation of the ultraviolet flux and the width of the Ly α profile on the spin period of the white dwarf (Gänsicke, Beuermann & de Martino 1995;Gänsicke et al 1998Gänsicke et al , 2006Schwope et al 2002;Araujo-Betancor et al 2005;Szkody et al 2010b). Assuming the presence of a weak magnetic field (B), we can calculate the minimum magnitude required by the white dwarf to decouple the electron spin and detect splitting of sharp metal lines with the spectral resolution of COS.…”
Section: An Accretion Spot On a Magnetic White Dwarfmentioning
confidence: 99%